Transformasi Digital Pada UMKM Dalam Meningkatkan Daya Saing Pasar - Putra, Toni Wijanarko Adi; Solechan, Achmad; Hartono, Budi (Universitas PGRI Semarang, 2023)
The phenomenon of digital transformation in MSMEs can be observed from several aspects, including: resource challenges during digital transformation because transformation, like any change, requires resources. Another phenomenon is organizational barriers: such as lack of financial resources, lack of management support, resistance to change, and lack of infrastructure. Technological barriers due to lack of knowledge, SMEs hesitate to implement advanced technology services, for example Enterprise Resource Planning (ERP) technology innovations, and artificial intelligence, as well as legal barriers related to lack of cooperation and integration between management and departments, as well as privacy issues. The technique in data analysis in this study used a literature review study. The results of the study show that there are multiple opportunities and attention for MSMEs, where there is a special need for MSMEs to carry out digital transformation in order to increase business competitiveness and expand market share. With digital transformation, product downstreaming processes and operations from producers to consumers will increase, service speed, better trust, secure data exchange platforms but also opportunities for digital transformation. With digital transformation, it will form a new digital entrepreneurial ecosystem that is able to compete with international competitors. By carrying out digital transformation, MSMEs can increase competitive advantage and expand market reach, increase operational efficiency by reducing time and costs for business activities, and increasing market access or downstreaming to consumers.